Development of a Competency-Based Principal Policy Model to Improve the Quality of Graduates. - Rita Siryani (Yayasan Darussalam Bengkulu, 2025)
Enhancing the quality of vocational secondary school graduates is a strategic imperative for strengthening workforce competitiveness and alignment with the evolving demands of industry. However, school principals’ policies in several vocational high schools remain insufficiently integrated with national competency standards and workplace expectations. This study aimed to develop and validate a principal policy model designed to improve graduate quality through strengthened competency-based school management and industry relevance. The study employed a Research and Development approach using the 4D model, comprising the define, design, develop, and disseminate stages. It was conducted across five public vocational high schools in Bengkulu and involved 50 school principals, 200 teachers, and 500 students. Data were collected through questionnaires, interviews, document analysis, and expert-validation instruments, and were analysed using descriptive quantitative and qualitative techniques. The resulting model consisted of four core components: competency-based strategic planning, teachers’ professional development, instructional monitoring and evaluation, and strengthened school–industry partnerships. Expert validation yielded an Aiken’s V coefficient of 0.87, indicating a very high level of content validity. Field testing demonstrated a 25% improvement in graduates’ work-competency indicators, with statistically significant differences observed (p < .05). These findings indicate that the developed model is practical and effective in improving curriculum relevance and graduate preparedness for the world of work. Nevertheless, the study was limited to vocational schools in Bengkulu; therefore, future research should examine the model’s effectiveness across broader provincial or national contexts.